Stilistik-Estetik Epilog Kakawin Abad XX Karya Made Degung - Anak Agung Gde Alit Geria; I Made Bendi Yudha (Mudra Jurnal Seni Budaya, 2022)
Kakawin (manuscript), composed by Rakawi Made Degung from Sibetan Karangasem, received a positive response among lovers of classical Balinese literature, because it is full of Shiva-Buddhist philosophy which until now still lives side by side and harmoniously in Bali. This well-packaged, aesthetically pleasing Kakawin has an important position among the existing kakawin, because the content and unique presentation factor is the spirit of the times, namely the Shiva-Buddhist discourse that is typical of the Balinese model. This Kakawin was completed on Friday Paing Sinta, the 13th anniversary of the Saka year 1915 (1993 AD). The information implied in this kakawin epilogue is truly something unique that is rarely or never found in other kakawin. His Kakawin compositions, the writing of the number of years to the name of the pangawi (author) and its origin, are packaged in a unique way and explained in one last stanza of this kakawin. In addition to starting with the Manggala who worships the Goddess of Beauty (Saraswati) as the sacred God Brahma spouse, the Goddess of Knowledge, and the Soul of the script, at the end of his work, Pangawi begs before Him so that the world will be saved as well as its leader.